Atimoi and agogimoi: Reflections on debt slavery in archaic Athens (Dike - Rivista di Storia del Diritto Greco ed Ellenistico, 2022)
Debt enslavement of Athenians before Solon’s Seisachtheia is well documented. The main sources are Solon (fr. 4 and 36 W), Aristotle ([Arist.] Ath. Pol. 2.2.) and Plutarch (Sol. 13.2-3), among others. However, there are discrepancies between the sources and many doubts about this topic. Solon’s law of amnesty (Plut. Sol. 19.4) was probably part of the measures aimed at eliminating debt slavery. The intention here is to shed further light on this issue by analysing the meaning of atimos and agogimos in relation to the situation of debtors at the time